Pengaruh Kualitas Pelayanan terhadap Kepuasan Berkunjung di Destinasi Pemandian Air Panas Pariban Berastagi - Yola Bedyanina Barus; Ika Mary (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Pariban Hot Springs is one of the most visited tourist destinations by tourists. Apart from being a very nice destination, the cool air also attracts visitors to visit these destinations. However, the quality of a tourist destination is not only determined by the beauty of the tourist object, but must be supported by the quality of service so that visitors will feel satisfied and intend to visit again. Therefore the purpose of this research is to find out how the influence of service quality on visitor satisfaction. This research uses associative quantitative research methods with a sample of 100 respondents. The method of analysis in this study is multiple linear regression with partial hypothesis testing (t test) and simultaneous testing (f test). From the test results of this study, it was found that partially the reliability and empathy variables had a significant influence on visiting satisfaction while the variables of responsiveness, assurance and physical evidence did not show a significant effect. Simultaneously the variables of reliability, responsiveness, assurance, empathy and tangibles together have a significant effect on visiting satisfaction.